Sero-epidemiological investigation and cross-neutralization activity against SARS-CoV-2 variants in cats and dogs, Thailand - Suwanpakdee, Sarin; Ketchim, Natthaphat; Thongdee, Metawee; Chaiwattanarungruengpaisan, Somjit; Tangsudjai, Siriporn; Wiriyarat, Witthawat; Julapanthong, Pruksa; Trakoolchaisri, Wachira; Buamas, Supakit; Sakcamduang, Walasinee; Okada, Pilailuk Akkapaiboon; Puthavathana, Pilaipan; et al. (Frontiers in Veterinary Science, 2024)
Epidemiological data on SARS-CoV-2 infection in companion animals have been thoroughly investigated in many countries. However, information on the neutralizing cross-reactivity against SARS-CoV-2 variants in companion animals is still limited. Here, we explored the neutralizing antibodies against SARS-CoV-2 in cats and dogs between May 2020 and December 2021 during the first wave (a Wuhan-Hu-1-dominant period) and the fourth wave (a Delta-dominant period) of the Thailand COVID-19 outbreak. Archival plasma samples of 1,304 cats and 1,795 dogs (total = 3,099) submitted for diagnosis and health checks were collected at the Prasu-Arthorn Veterinary Teaching Hospital, Faculty of Veterinary Science, Mahidol University, Nakhon Pathom. A microneutralization test was used to detect neutralizing antibodies against the ancestral Wuhan-Hu-1 and the Delta variants. A plasma sample with neutralizing titers ≥10 was considered positive. Our results showed relatively low seroprevalence with seropositive samples detected in 8 out of 3,099 individuals (0.26, 95% CI 0.11–0.51%). Among these cases, SARS-CoV-2 neutralizing antibodies from both the ancestral Wuhan-Hu-1 and the Delta variants were found in three out of eight cases in two cats (n = 2) and one dog (n = 1). Furthermore, neutralizing antibodies specific to only the ancestral Wuhan-Hu-1 variant were exclusively found in one cat (n = 1), while antibodies against only the Delta variant were detected in four dogs (n = 4). Additionally, the neutralizing cross-activities against SARS-CoV-2 variants (Alpha, Beta, and Omicron BA.2) were observed in the seropositive cats with limited capacity to neutralize the Omicron BA.2 variant. In summary, the seropositivity among cats and dogs in households with an unknown COVID-19 status was relatively low in Thailand. Moreover, the neutralizing antibodies against SARS-CoV-2 found in the seropositive cats and dogs had limited or no ability to neutralize the Omicron BA.2 variant. Thus, monitoring SARS-CoV-2 infection and sero-surveillance, particularly in cats, is imperative for tracking virus susceptibility to the emergence of new SARS-CoV-2 variants.